ACTIVITIES OF INCLUSIVE RESOURCE CENTERS IN MOUNTAIN AREAS - Matveieva, Nataliia (Mountain School of Ukrainian Carpaty, 2021)
The urgency of the problem lies in the ever-growing number of children with disabilities in Ukraine, the need to provide them with appropriate assistance from specialists and the existing obstacles to the development of inclusive infrastructure in the mountain villages of our country. Remoteness, poor transport links, lack of qualified specialists, incomplete awareness of the population hinder the development of inclusive education, prevent its receipt by people with special needs. The purpose of the article is to analyze the specifics of the activities of inclusive resource centers that provide assistance to teachers, parents and children with disabilities living in mountainous areas of Ukraine. We used theoretical (analysis and generalization of psychological and pedagogical literature) and empirical methods (surveys, interviews, observations, methods of statistical data processing). The article raises the issue of development of inclusive education in rural (mountainous) areas of Ukraine. The main factors influencing this process are considered, the peculiarities of providing high-quality correctional and developmental, psychological and pedagogical services to children with special educational needs living in mountainous areas are analyzed. The results of the study showed that the activities of specialists of inclusive resource centers to provide assistance to teachers, parents and, in particular, children with disabilities living in remote areas, is of great importance for personal development of students and professional activities of teachers, parental awareness. The issue reaches the national scale, as evidenced by the activity in expanding the regulatory framework, government allocations for the development of inclusion. However, the problem is not fully explored today and needs further in-depth study.